Detecting Sleep Apnea with Smart-tech: Scientific Breakthrough or Overhyped Technology? - Aleksandra Głowacka; Paulina Grzeszczuk; Iwona Skorulska; Agnieszka Kalisz; Marta Ignatiuk-Chilkiewicz; Weronika Grywińska; Julia Kozakiewicz; Kamil Kościelecki; Klaudia Mączewska; Patrycja Długozima (Quality in Sport)
Introduction: This review paper seeks to examine the existing knowledge on the underlying mechanisms of sleep apnea, the complexities associated with its diagnosis, and the potential of cutting-edge wearable technology to enhance its detection.